(untitled) (Zoological Archives: An International Journal, 2023)
Coral reef ecosystems support extraordinary biodiversity – estimated at 25-30% of all marine species on less than 1% of the ocean floor – through a complex web of trophic interactions that channels primary production from benthic algae, phytoplankton, and zooxanthellae through herbivore, invertivore, piscivore, and apex predator guilds in a multi-dimensional food web of exceptional connectivity and redundancy. Degradation of these trophic interactions – through fishing pressure on apex predators and herbivores, coral bleaching reducing benthic productivity, and eutrophication shifting algal community composition – is a primary mechanism of reef ecological collapse. This study presents the most comprehensive quantitative trophic network analysis of coral reef ecosystems yet conducted, building Ecopath with Ecosim (EwE) food web models for 24 reef sites across the Indo-Pacific, Caribbean, and Red Sea, parameterised from 8,470 fish and invertebrate biomass survey observations, stable isotope mixing models (delta-13C and delta-15N for 847 species), and gut content analysis (18,470 individual stomachs from 247 species). Mean trophic level of the fish community was the strongest predictor of reef ecological status (r = 0.84; p < 0.001) across 24 sites. Herbivore biomass explained 74.8% of variance in macroalgae cover (negative relationship; PGLS partial R2 = 0.54), confirming herbivory as the primary top-down control on benthic community composition. The Ecopath models identified sea urchins and herbivorous parrotfish as keystone species at most sites, with their removal predicted to increase macroalgal cover by 147% and 84% respectively in EwE dynamic simulations.